Pre-treatment and extraction techniques for recovery of added value compounds from wastes throughout the agri-food chain. Issue 23 (19th October 2016) - Arshadi, Mehrdad; Attard, Thomas M.; Lukasik, Rafal M.; Brncic, Mladen; da Costa Lopes, André M.; Finell, Michael; Geladi, Paul; Gerschenson, Lia Noemi; Gogus, Fahrettin; Herrero, Miguel; Hunt, Andrew J.; Ibáñez, Elena; et al.
Abstract : The enormous quantity of food wastes discarded annually forces a look into alternatives for this interesting feedstock. Abstract : The enormous quantity of food wastes discarded annually forces a look into alternatives for this interesting feedstock. Thus, food bio-waste valorisation is one of the current imperatives of society. This review is the most comprehensive overview of currently existing technologies and processes in this field. It tackles classical and innovative physical, physico-chemical and chemical methods of food waste pre-treatment and extraction for the recovery of added value compounds and detection by modern technologies and is an outcome of the COST Action EUBIS, TD1203 Food Waste Valorisation for Sustainable Chemicals, Materials and Fuels.